Academic Orthopaedics As a Driver of Gender Diversity in the Orthopaedic Workforce: A Review of 4, 519 Orthopaedic Faculty Members. (February 2022) - Kuhns, Benjamin; Haws, Brittany E.; Kaupp, Shannon; Maloney, Michael D.; Carmody, Emily E.; Mannava, Sandeep
Abstract : Background: The purpose of this study was to perform a cross-sectional analysis on the gender composition of practicing academic orthopaedic surgeons using three databases composed of clinical orthopaedic surgeons. Methods: A comprehensive database of 4, 519 clinically active academic orthopaedic surgeons was compiled for this study after the review of publicly available data. The complied data set was evaluated alongside orthopaedic databases obtained from the 2017 Association of American Medical Colleges (AAMC) Faculty Administrative Management Online User System and the 2016 American Academy of Orthopaedic Surgery (AAOS) Orthopaedic Practice in the US census representing the entire academy membership orthopaedic workforce. Gender status was obtained and compared between the three databases. Results: Of the 4, 519 clinically active academic orthopaedic surgeons analyzed, 435 (10%) were female compared with 19% for the AAMC faculty database and 7% for the AAOS members. Fourteen percent of women had achieved the rank of professor compared with 25% of the men ( P < 0.001). AAMC faculty had a significantly higher percentages of female representation compared with both the clinical faculty (19% versus 10%; P < 0.001) and AAOS members (19% versus 7%; P < 0.001). Conclusion: Despite multiple initiatives designed to increase diversity, the 7% female representation in the orthopaedic workforce identified in this study remains markedly lower than other medical and surgical specialties. A higher percentage of women were associated with the AAMC orthopaedic faculty compared with clinically active female surgeons at these institutions. Academic orthopaedic surgeons had greater female representation than the general orthopaedic workforce, highlighting the importance of training institutions at promoting gender equity.